Oxidative Stress-Mediated YAP Dysregulation Contributes to the Pathogenesis of Pemphigus Vulgaris - Huang, Yunying; Jedličková, Hana; Cai, Yang; Rehman, Ambreen; Gammon, Luke; Ahmad, Usama Sharif; Uttagomol, Jutamas; Parkinson, Eric Kenneth; Fortune, Farida; Wan, Hong (Frontiers in Immunology, 2021)
Pemphigus Vulgaris (PV) is a life-threatening autoimmune disease manifested with blisters in the skin and mucosa and caused by autoantibodies against adhesion protein desmoglein-3 (Dsg3) expressed in epithelial membrane linings of these tissues. Despite many studies, the pathogenesis of PV remains incompletely understood. Recently we have shown Dsg3 plays a role in regulating the yes-associated protein (YAP), a co-transcription factor and mechanical sensor, and constraining reactive oxygen species (ROS). This study investigated the effect of PV sera as well as the anti-Dsg3 antibody AK23 on these molecules. We detected elevated YAP steady-state protein levels in PV cells surrounding blisters and perilesional regions and in keratinocytes treated with PV sera and AK23 with concomitant transient ROS overproduction. Cells treated with hydrogen peroxide also exhibited augmented nuclear YAP accompanied by reduction of Dsg3 and α-catenin, a negative regulator of YAP. As expected, transfection of α-catenin-GFP plasmid rendered YAP export from the nucleus evoked by hydrogen peroxide. In addition, suppression of total YAP was observed in hydrogen peroxide treated cells exposed to antioxidants with enhanced cell-cell adhesion being confirmed by decreased fragmentation in the dispase assay compared to hydrogen peroxide treatment alone. On the other hand, the expression of exogenous YAP disrupted intercellular junction assembly. In contrast, YAP depletion resulted in an inverse effect with augmented expression of junction assembly proteins, including Dsg3 and α-catenin capable of abolishing the effect of AK23 on Dsg3 expression. Finally, inhibition of other kinase pathways, including p38MAPK, also demonstrated suppression of YAP induced by hydrogen peroxide. Furthermore, antioxidant treatment of keratinocytes suppressed PV sera-induced total YAP accumulation. In conclusion, this study suggests that oxidative stress coupled with YAP dysregulation attributes to PV blistering, implying antioxidants may be beneficial in the treatment of PV.